Electrocatalytic properties of graphite intercalation compound with metal chlorides modified by cathodic treatment. (20th February 2019) - Rozmanowski, T.; Krawczyk, P.
Abstract: The structural, morphological and electrochemical properties of electrochemically exfoliated NiCl2 -FeCl3 -PdCl2 -graphite intercalation compound (NiCl2 -FeCl3 -PdCl2 -GIC) were studied in this work. The synthesis of NiCl2 -FeCl3 -PdCl2 -GIC was based on a molten salts method using purified flaky graphite and anhydrous chlorides of Ni, Fe and Pd as reactants. The intercalation process was carried out for 72 h at 450 °C. Cathodic exfoliation of NiCl2 -FeCl3 -PdCl2 -GIC was performed in 6 M KOH solution by combined potentiodynamic and potentiostatic methods. The characterization of the crystalline structure and morphological properties of original as well as exfoliated GIC were studied using the XRD and SEM techniques. The electrochemical activity of the investigated materials was examined on the model reaction of methanol oxidation conducted by cyclic voltammetry and potentiostatic method. The XRD and SEM analysis revealed that the stage of exfoliation depends on the applied reduction potential. It is also found that exfoliation degree increases with the number of voltammetric cycles performed during the exfoliation process. Electrochemical measurements showed that electrochemical exfoliation of NiCl2 –FeCl3 –PdCl2 –GIC caused by its cathodic treatment has a significant influence on the electrochemical activity of the examined GIC towards methanol electrooxidation. Highlights: Ternary NiCl2 -FeCl3 -PdCl2 -GIC with a mixed of stages-3, 4 was obtained. Electrochemical exfoliation of GIC leads to structural and morphological changes. Exfoliation of GIC increases its electroactivity towards methanol oxidation.